2023
DOI: 10.1101/2023.01.06.23284269
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Adipokine levels and their association with clinical disease severity in patients with dengue

Abstract: Adipokines have not been studied in acute dengue, despite their emerging role in inducing and regulating inflammation. Therefore, we sought to identify adipokine levels in patients with varying severities of acute dengue to understand their role in disease pathogenesis. We determined the levels of leptin, resistin, omentin, adiponectin, as well as IFNβ, and NS1 using quantitative ELISA in patients with dengue fever (DF=49) and dengue haemorrhagic fever (DHF=22) at admission (febrile phase) and at the time of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…However, one large cohort found that liver impairment was significantly more common among women, 40 questioning the impact of sex on dengue‐associated liver involvement. In one study, severe hepatitis defined as AST and/or ALT>1,000IU/L was significantly associated with obesity 73 and in another study, omentin and serum leptin levels in the febrile phase correlated with AST and ALT levels 168 …”
Section: Resultsmentioning
confidence: 96%
“…However, one large cohort found that liver impairment was significantly more common among women, 40 questioning the impact of sex on dengue‐associated liver involvement. In one study, severe hepatitis defined as AST and/or ALT>1,000IU/L was significantly associated with obesity 73 and in another study, omentin and serum leptin levels in the febrile phase correlated with AST and ALT levels 168 …”
Section: Resultsmentioning
confidence: 96%